(untitled) (Altre Modernità, 2024)
Louise Ann Wilson, Sites of Transformation: Applied and Socially Engaged Scenography in Rural Landscapes (London and New York, Methuen Drama, 2022, 233 pp. ISBN 978-1-3502-8275-9) by Harriet Carnevale